Trabajo social comunitario y su incidencia en la calidad de vida de las mujeres del barrio Venezuela del cantón Machala - Armijos Chávez, Yaritza Marisol (My University, 2020)
The present investigation denotes the importance of the social worker in the community context towards the guarantee of the quality of life for people of an urban territory, who share the same collective experiences and problems, directed to solve their lacks. In fact, it is necessary to implement a series of methodological stages, to highlight the intervention model that determines the process to be followed, the important moments of community intervention that promote the degree of participation of the subjects in search of improving these conflicts as an opportunity for development. Therefore, it is necessary to analyze the incidence of community social work in the generation of quality of life of the members of a given sector through the bibliographic research indexed in the database. The investigation demonstrates a qualitative approach because these researchers analyze the different social realities as facts that need to be resolved, the life perspective of the communities and the actions taken in the face of their difficulties, the services that are lacking or within their reach. The cited authors express that community social work is directed towards the involvement with large minorities established in a territorial environment, which fosters the liberation of conflicts, needs and insufficiencies, promoting change by means of organization, intension for the generation of quality of life guaranteed by the State offers to all its citizens, which integrates a welfare of satisfaction in the different sectors (work, health, housing, access to education, among others) that allow the human being to develop adequately.
La presente investigación denota la importancia del trabajador social en el contexto comunitario hacia la garantía de la calidad de vida para personas de un territorio urbano, que comparten las mismas vivencias y problemas colectivos, direccionados a solventar sus carencias. En efecto, es necesario implementar una serie de etapas metodológicas, destacar el modelo de intervención que determina el proceso a seguir, los momentos importantes de la intervención comunitaria que promueven el grado de participación de los sujetos en busca de mejorar dichos conflictos como oportunidad de desarrollo. Por ende, es preciso analizar la incidencia del trabajo social comunitario en la generación de calidad de vida de las personas miembros de un sector determinado mediante la pesquisa bibliográfica indexada en la base de datos. La investigación demuestra un enfoque cualitativo debido a que estos investigadores analizan las distintas realidades sociales como hechos que necesitan resolverse, la perspectiva de vida de las comunidades y las actuaciones frente a sus dificultades, a los servicios que carecen o están a su alcance. Los autores citados expresan que el trabajo social comunitario está direccionado hacia el involucramiento con las grandes minorías establecidas en un entorno territorial, que fomenta la liberación de conflictos, necesidades e insuficiencias, promoviendo al cambio mediante la organización, intensión para la generación de calidad de vida garantía del Estado ofrece a todos sus ciudadanos, que integra un bienestar de satisfacción en los distintos sectores (trabajo, salud, vivienda, acceso a la educación, entre otras) que le permiten al ser humano desarrollarse adecuadamente.
Keywords: TRABAJO SOCIAL; INTERVENCION COMUNITARIA; CALIDAD DE VIDA